Effect of salinity on agro-morphogenic traits of tomatillo genotypes (Progressive Agriculture, 2022)
A pot experiment was conducted in the net house of Department of Genetics and Plant Breeding, Sher-e-Bangla Agricultural University, Dhaka-1207, Bangladesh, during the period of November, 2017 to March, 2018 to observe the performance of four tomatillo genotypes under three salinity (NaCl) treatments based on their agro-morphogenic traits. A two factorial experiment was conducted which included four tomatillo genotypes (Factor A) viz. G1 (SAU tomatillo 1), G2 (SAU tomatillo 2), G3 (PI003), G4 (PI004) and two salinity (NaCl) treatments with a control (Factor B) viz. T1 (Control), T2 (8 dS/m), T3 (12 dS/m) and was outlined in Completely Randomized Design (CRD) with three replications. The observed results showed that, both of four tomatillo genotypes (G) and three salinity treatments (T) had their independent significant influence and also had significant influence in their G×T interaction between different agro-morphogenic traits. Almost all traits responded negatively (%reduction) under the increased level of salinity treatments. Considering the minimum %reduction in yield and its contributing traits under both slightly (T2: 8 dS/m) and moderately (T3: 12 dS/m) salinity condition, genotype G1 and G3 could be recommended for cultivation and further trial in the salinity affected southern region of Bangladesh. The maximum reduction in days to maturity was found in genotype G1 and G4 and could be served as parent materials for further hybridization or genetic transformation program.Progressive Agriculture 32 (2): 140-150, 2021